Some observations on the prawn fishery of Cochin - Suseelan, C; Rajan, K N; Nandakumar, G (Indian Journal of Fisheries, 2011)
Shrimp fishery bas played an importantrole in the socioeconomic growth of theCoastal people in recent years. Prawn fishingis practised throughout the 590 Ian coast lineof Kerala, but in the past 3 -4 decades this.. industry has shown a remarkable developmentdue to the mechanized fishing and processingof seafoods